1982
DOI: 10.1111/j.1469-8137.1982.tb03349.x
|View full text |Cite
|
Sign up to set email alerts
|

PHYTOLECTINS FROM THE NITROGEN‐FIXING LICHEN PELTIGERA HORIZONTALIS: THE BINDING PATTERN OF PRIMARY PROTEIN EXTRACT

Abstract: SUMMARYA protein fraction containing phytolectins was isolated from the nitrogen-fixing lichen Peltigera horizontalis. These lectins were thermostable, truly non-specific and were more effective on human erythrocytes A, B and O than concanavalin A. Phytolectins originate from the mycobiont and do not bind any of the freshly isolated phycobionts tested, but with slight differences bind the cultured phycobionts isolated from three Peltigera spp. It is suggested that the production of phytolectins may be characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

1983
1983
2000
2000

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 24 publications
3
24
0
1
Order By: Relevance
“…The phytolectin of P. canina var canina is thermostable. As previously described by Howe and Barrett (1970) in Parmelia michauxiana and by Petit (1982) in Peltigera horizontalis, who showed an agglutinating activity at the primary protein extract level, the phytolectin of P. canina var canina is thermostable in the same condition (10 min at 105 °C). We also note that the agglutinating activity of this phytolectin may be considerably stimulated by numerous divalent cations (Mg2+, Mn2+, Ca2+, Co^^, Cu2+) which abound in lichen thalli, well known for their capacity to retain such compounds.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The phytolectin of P. canina var canina is thermostable. As previously described by Howe and Barrett (1970) in Parmelia michauxiana and by Petit (1982) in Peltigera horizontalis, who showed an agglutinating activity at the primary protein extract level, the phytolectin of P. canina var canina is thermostable in the same condition (10 min at 105 °C). We also note that the agglutinating activity of this phytolectin may be considerably stimulated by numerous divalent cations (Mg2+, Mn2+, Ca2+, Co^^, Cu2+) which abound in lichen thalli, well known for their capacity to retain such compounds.…”
Section: Resultssupporting
confidence: 68%
“…In some cases, phytolectins have been shown to bind to the appropriate phycobiont (Lockhart et a/., 1978;Bubrick, Galun and FrensdorflF, 1981;Petit, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…These prokaryotes are hosted either by fungi in the lichen symbiosis or in vascular plants in associations of the Anabaena-Azolla (Peters et al, 1982) or Nostoc-Gunnera (Schaede, 1951) type. Studies on various lichens (Lockhart et al, 1978;Petit, 1978;Petit et al, 1983) led to the isolation of a lectin that apparently belonged to the fungal partner and that might be able to recognize structures on the cyanobacterium wall; the physiological relationship of the two partners may be modulated by variations in the sugars present on the wall of the phycobiont. Similarly, studies (Mellor et al, 1981;Ladha and Watanabe, 1984;McCowen et al, 1987) of the AnabaenaAzolla symbiosis have shown that a lectin belonging to the fern, and which differs according to the species, specifically recognizes the strain of cyanobacterium for which it adapted.…”
mentioning
confidence: 99%
“…The participation of this class of proteins as a recognition factor for the association of compatible fungi and algae in lichen symbiosis has been suggested (Lockhart et al, 1978 ;Petit, 1982 ;Petit et al, 1983) as an extension of the concept of interaction between pathogenic fungi and their hosts (Rose! n et al, 1996) and many other biological systems where lectins act as recognition molecules (Sharon & Lis, 1989).…”
Section: mentioning
confidence: 99%